Upaya Diplomasi Publik Korea Selatan Dalam Menyebarkan Hallyu Di Amerika Serikat Pada Pemerintahan Moon Jae In - Niju Fayza; Anita Afriani Sinulingga; Inda Mustika Permata (Andalas Institute of International Studies, 2022)
Relations between the United States and South Korea during the Moon Jae In Administration experienced ups and downs that impacted South Korea's security problems. In addition, the United States's public sentiment towards South Korea still shows a high number compared to other countries. However, the spread of hallyu turned out to be successful with the decline in United States public sentiment towards South Korea and hallyu from 35.6% in 2017 to 16.5% in 2020. This study aims to analyze South Korea public diplomacy efforts in spreading hallyu to the United States in order to improve their relations and the image of South Korea as an attractive country as stated in Public Diplomacy Act 2017-2021. This study uses a qualitative method with a descriptive analytical approach and utilizes data from secondary sources. This study uses Fitzpatrick's concept of public diplomacy which divides public diplomacy activities into six indicators. Based on Fitzpatrick's concept of public diplomacy, this study finds that there are five activities, advocacy of South Korean policies and culture through digital, communication of the South Korean government elite, building long-term relationships with various actors, promoting arts and culture by holding hallyu festivals, movie nights, and exhibitions, as well as providing political assistance to the United States. Interestingly, this research found that the South Korean government often included hallyu stars in most of its activities which accelerating the spread of hallyu in the United States.